DETERMINANT OF INVESTMENT DECISIONS: EVIDENCE FROM GEN Z IN INDONESIA - Saputra, Upayana Wiguna Eka; Elfarosa, Ketut Vini (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2023)
This study is aimed to determine the effect of stock influencers and consumer trust on investment decisions through perceived risk as moderating. The research in this study was a quantitative research used a non-probability sampling technique, by applying the quota sampling method to take a sample of 100 respondents. The data analysis technique in this study used Partial Least Square (PLS). PLS is a Structural Equation Model (SEM) equation model using an approach based on variance or component-based structural equation modeling. The results of this study are: (1) Stock influencers have a positive and significant effect on consumer trust. (2) Consumer trust has a positive and significant effect on investment decisions. (3) Consumer trust has a positive and significant effect on investment decisions. (4) Consumer trust has a positive and significant effect on investment decisions by moderating perceived risk. This shows that perceived risk can moderate the effect that the better or the worse a person's consumer trust will be, will affect one's investment decisions with perceived risk as moderating. Based on this description, further researchers can use qualitative approaches such as interviews to provide a stronger understanding of the factors that can influence investment decisions. Likewise for students, it is hoped that they can increase literacy regarding perceived risk so that they make decisions to invest more accurately.